PELLET WATER STABILITY STUDIES ON LUPIN MEAL BASED SHRIMP (Penaeus monodon) AQUACULTURE FEEDS : COMPARISON OF LUPIN MEAL WITH OTHER DIETARY PROTEIN SOURCES - Agung Sudaryono (JOURNAL OF COASTAL DEVELOPMENT, 2001)
Nutritional quality of lupin based shrimp (Penaeus monodon) aquaculture feeds was evaluated in terms of pellet water stability. Two series of water stability experiments were carried out to study the effects of lupin meal inclusions as an dietary protein alternative for fish meal (Experiment 1) and soybean meal (Experiment 2) on percentage dry matter and protein leachings of the compounded test diets. Increasing the replacement levels of dietary fish meal with lupin meal resulted in significant decrease (P<0.05) of pellet water stability over the 480-minute immersion period. A significant improvement in water stability with the increase of the soybean meal replacement levels with lupin meal up to 50% was found, however, further increase above 50% substitution level resulted in reduced water stability of the diets. It is concluded that lupin meal can not totally replace either fish meal or soybean meal in shrimp formulated diets and a 50% replacement level of dietary fish meal or dietary soybean meal with lupin gives a promising good result in terms of pellet water stability for P. monodon diets.